2012
DOI: 10.1088/0004-637x/754/1/49
|View full text |Cite
|
Sign up to set email alerts
|

THE LICK AGN MONITORING PROJECT 2011: DYNAMICAL MODELING OF THE BROAD-LINE REGION IN Mrk 50

Abstract: We present dynamical modeling of the broad line region (BLR) in the Seyfert 1 galaxy Mrk 50 using reverberation mapping data taken as part of the Lick AGN Monitoring Project (LAMP) 2011. We model the reverberation mapping data directly, constraining the geometry and kinematics of the BLR, as well as deriving a black hole mass estimate that does not depend on a normalizing factor or virial coefficient. We find that the geometry of the BLR in Mrk 50 is a nearly face-on thick disk, with a mean radius of 9.6 +1.2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 40 publications
4
93
0
Order By: Relevance
“…By using Bayesian probability theory and Monte Carlo algorithms, Pancoast et al (2011) presented a general method for geometric and dynamical modelling of the BLR. Using this method, Brewer et al (2011) and Pancoast et al (2012) modelled the geometry and estimated the BH mass for the Seyfert 1 galaxies Arp 151 and Mrk 50. In both studies evidence for a disk-like BLR geometry was found.…”
Section: Introductionmentioning
confidence: 99%
“…By using Bayesian probability theory and Monte Carlo algorithms, Pancoast et al (2011) presented a general method for geometric and dynamical modelling of the BLR. Using this method, Brewer et al (2011) and Pancoast et al (2012) modelled the geometry and estimated the BH mass for the Seyfert 1 galaxies Arp 151 and Mrk 50. In both studies evidence for a disk-like BLR geometry was found.…”
Section: Introductionmentioning
confidence: 99%
“…This allows to make a measurement of the black hole mass that does not depend on the virial coefficient (Pancoast et al, , 2012. The accuracy of the black hole mass estimates with this method has been significantly improved (Barth et al, 2011;Pancoast et al, 2012;Li et al, 2013). The preliminary results show that five black hole masses have been measured at an uncertainty of ∼ 0.2 − 0.4 dex depending upon data quality with this method (Pancoast et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Recently, Pancoast et al (2011) proposed a method to analyze reverberation mapping data, with which the geometry and kinematics of the BLR can be well constrained by modeling the continuum light curve and broad line profiles directly with the velocity resolved broad line data. This allows to make a measurement of the black hole mass that does not depend on the virial coefficient (Pancoast et al, , 2012. The accuracy of the black hole mass estimates with this method has been significantly improved (Barth et al, 2011;Pancoast et al, 2012;Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These types of programs will or already are leading to RM-based mass measurements that are independent of other methods (i.e., do not depend on f ). I show a couple examples of the products from these types of analyses in In a similar, though effectively opposite approach, the Bayesian analysis software of Pancoast et al [26] uses dynamical models of the BLR with possible geometries in combination with the reverberation campaign spectra and light curves to derive the BH mass and constrain the BLR geometry (see Figure 3). This modeling process can also output the 2D velocity delay map as a product, but more importantly, this dynamical modeling results in an independent estimate of the black hole mass, i.e., one that does not depend on f .…”
Section: Recent Advances In Reverberation Mapping Analyses: Velocity mentioning
confidence: 99%